OPTIMASI YIELD ETIL P METOKSISINAMAT PADA EKSTRAKSI OLEORESIN KENCUR (Kaempferia galanga) MENGGUNAKAN PELARUT ETANOL - Setyawan, Eko; Putratama, Pandhu; Ajeng, Asriningtyas; Pita Rengga, Wara Dyah (Jurnal Bahan Alam Terbarukan, 2012)
Kencur (Kaempferia galanga L.) banyak digunakan sebagai bahan baku obat tradisional (jamu), fitofarmaka, industri kosmetika, industri makanan, dan industri insektisida. Minyak atsiri rimpang kencur mengandung etil sinnamat dan metil p-metoksi sinamat (EPMS). Ekstraksi oleoresin kencur dilakukan dengan etanol sebagai pelarut. Optimasi yield EPMS diteliti terhadap perbandingan massa serbuk kering kencur dan etanol dan waktu ekstraksi. Perbandingan kencur : etanol yang digunakan adalah 1 : 2, 1 : 3, dan 1 : 4. Waktu operasi yang digunakan adalah 2 s.d 5 jam. Tahapan proses ekstraksi oleoresin kencur adalah preparasi bahan, ekstraksi, evaporasi dan pemurnian. Oleoresin hasil ekstraksi dianalisis dengan uji GC-MS untuk mengetahui kandungan EPMS dan kandungan minyak atsiri lain dalam oleoresin kencur. Oleoresin hasil ekstraksi berwarna coklat tua dengan yield antara 6-8%. Kandungan EPMS dalam oleoresin bervariasi antara 67,77 hingga 87,57%. Massa oleoresin optimal hasil ekstraksi adalah 6,09 gram pada perbandingan kencur dan etanol 1:4 selama 4 jam. Pendekatan persamaan hasil ekperimen ekstraksi kencur dan etanol menghasilkan titik optimal EPMS pada waktu ekstraksi 3,62 dengan massa EPMS 6,04 gram Lesser galangal (Kaempferia galanga L.) is widely used as a traditional medicine (herbal medicine), fitofarmaka, cosmetics industry, food industry, and insecticide industry. The essential oils in the Lesser galangal contain ethyl sinnamat and methyl p-methoxy cinnamic (EPMS). The oleoresin extraction of Lesser galangal was performed using ethanol as a solvent. Optimization of the EPMS yield was investigated to dry powder mass ratio of Lesser galangal and ethanol as well as the extraction time. The ratio of Lesser galangal : ethanol was varied from 1: 2, 1: 3 and 1: 4. The chosen operating time were 2 to 5 hours. The procedure of the oleoresin extraction process of Lesser galangal includes the preparation of materials, extraction, evaporation and purification. The extracted oleoresin was analyzed by GC-MS to determine the content of Ethyl P-methoxycinnamate (EPMS) and other volatile oil content in the oleoresin of Lesser galangal. The extracted oleoresin color was light brown to dark brown with the yield of between 6.31 to 8.3%. The EPMS content of the oleoresin varies between 67.77 to 87.57%. The optimum mass of the extracted oleoresin was 6.09 gram for 1:4 ratio of Lesser galangal : ethanol and 4 hours of the extraction time. The equation approach of the experimental results of Lesser galangal and ethanol produced the EPMS optimum point at the extraction time of 3.62 hours and EPMS mass of 6.04 grams.